Wrinkle sign for the Silfverskiöld test - Sanhudo, José Antonio Veiga; Canuto, Giorgio Marin (Journal of the Foot & Ankle, 2021)
Shortening of the triceps surae is evaluated using the Silfverskiöld test. The increase in dorsiflexion with the knee in flexion compared to the knee in extension makes the test positive. To perform the test, the examiner uses both hands and is not able to hold any device for objective measurement while assessing the magnitude of dorsiflexion. In view of this obstacle, this paper aims to describe a tip of a physical examination technique for evaluating the shortening of the triceps surae through the evaluation of the anterior wrinkle of the ankle. We performed the technique in a patient with shortening of the gastrocnemius and recorded the test, showing an increase in the anterior skinfold of the ankle. The test is simple, reproducible, requires no additional apparatus and shows variety in the severity of shortening. Level of Evidence V; Therapeutic Studies; Expert Opinion.